To solve the quadratic equation \( 2x^2 - 6 = 0 \) using the square root property, we can follow these steps:
-
Isolate the quadratic term: \[ 2x^2 = 6 \]
-
Divide both sides by 2: \[ x^2 = 3 \]
-
Apply the square root property (which states that if \( x^2 = a \), then \( x = \pm \sqrt{a} \)): \[ x = \pm \sqrt{3} \]
Thus, the solutions to the equation are: \[ x = \sqrt{3} \quad \text{and} \quad x = -\sqrt{3} \]
So, to enter the response for \( x \):
- One solution is \( x = \sqrt{3} \)
- The other solution is \( x = -\sqrt{3} \)
You can represent it concisely by saying: \[ x = \pm \sqrt{3} \]